The Mystery of the Image Display: The Leap from Technology to Art - Zhong, Zhirui (International Journal of Computer Science and Information Technology, 2024)
With the rapid evolution of electronic information technology, image presentation technology has penetrated from the simple domain of engineering to the core territory of artistic innovation. This thesis is intended to examine how digital tools have shaped the new landscape of visual expression art during this transformation and have brought profound transformative effects on the film and television industry. Firstly, this paper summarizes the historical context of image presentation technology, and compares the similarities and differences between past and present methods. Then, through the in-depth interpretation of the creation of internationally renowned digital art masters, we find how technological innovation has greatly enriched the form and connotation of innovation expression. In the cinematic arts in particular, advanced digital imaging has become an integral part of the field, as shown by the sophisticated computer-generated imagery (CGI) used in Avatar and the visual intelligence contained in Blade Runner 2049, both of which are stark examples of the power of technological and aesthetic fusion. It brings an unprecedented visual shock experience to the viewers. In addition, the paper also examines how experimental films can use high-tech means to break new ground, such as the immersive experience created by virtual reality technology. Finally, the paper discusses the reshaping of audience perception by digital process, and explores the prospect of the integration of technology and art in the future, emphasizing that despite the change of tools, the intrinsic value of art is still irreplaceable. The above review illustrates the key role of image display technology in cross-domain technology and art and its potential growth drivers.